A Decade of Prior Learning Assessment: A Systematic Review of Global Literature - Carrie J. Boden; Catherine A. Cherrstrom; Todd Sherron (Adult Education Research Conference, 2022)
Prior learning assessment (PLA) offers a powerful tool to adult learners. The purpose of this review was to systematically examine the global academic literature related to PLA over a decade.
Keywords: prior learning assessment (PLA); recognition of prior learning (RPL); prior learning assessment recognition (PLAR); systematic literature review; integrated literature review